RELATION OF RADIOGRAPHIC BI-RADS (4 AND 5) SCORE AND TRIPLE NEGATIVITY IN PATIENTS WITH BREAST CANCER - Farah Afzal,; Iffat Ara,; Ali, Azmat; Ayesha Jabeen,; Tahir, Sadia; Sadaf Aziz, (Journal of Ayub Medical College Abbottabad, 2025)
Background: Breast cancer is a disease in which cells in the breast grow out of control and form tumors. Lesion that has radiological features suggesting likelihood of cancer 2-10% is 4a, 10-50% is 4b, and 50-95% is 4c and more than 95% is BIRAD 5. Methods: This cross-sectional study was done at department of radiology, SKBZH CMH Muzaffarabad from Nov 2023 to March 2024. Our study included 100 patients having BI-RADS 4 and 5 confirmed by the sonomammography. Then all those patients underwent biopsy to check the triple negative status and the samples were sent for histopatholoical analysis. Data was analyzed using SPSS 21 version. Chi-square test was used to find the association between parameters. Results: A total of 100 patients were included in this study. The mean age of the patients was 48.45±14.663 years. A significant association of radiological grading (BIRADS 4 and 4) with triple negativity status and LN metastasis with p values 0.00 were found. A significant association of triple negativity with grades, LN metastasis, Necrosis, scars with p value 0.008, 0.016, 0.001, and 0.006 respectively were found. No significant association of size of tumor with radiological grading and triple negative status were found. Conclusion: Although, traditionally lesions with BI-RADS 5 score are considered more malignant than lesions with BI-RADS 4 score by clinicians in the daily practice, as pointed out in recent reports, TN have more frequent radiological BI-RADS 4 score.